Current issues in the evolutionary ecology of ant–plant symbioses. Issue 3 (21st January 2014) - Mayer, Veronika E.; Frederickson, Megan E.; McKey, Doyle; Blatrix, Rumsaïs
Summary: Ant–plant symbioses involve plants that provide hollow structures specialized for housing ants and often food to ants. In return, the inhabiting ants protect plants against herbivores and sometimes provide them with nutrients. Here, we review recent advances in ant–plant symbioses, focusing on three areas. First, the nutritional ecology of plant‐ants, which is based not only on plant‐derived food rewards, but also on inputs from other symbiotic partners, in particular fungi and possibly bacteria. Food and protection are the most important 'currencies' exchanged between partners and they drive the nature and evolution of the relationships. Secondly, studies of conflict and cooperation in ant–plant symbioses have contributed key insights into the evolution and maintenance of mutualism, particularly how partner‐mediated feedbacks affect the specificity and stability of mutualisms. There is little evidence that mutualistic ants or plants are under selection to cheat, but the costs and benefits of ant–plant interactions do vary with environmental factors, making them vulnerable to natural or anthropogenic environmental change. Thus, thirdly, ant–plant symbioses should be considered good models for investigating the effects of global change on the outcome of mutualistic interactions.   Contents     Summary 749 I. Introduction 749 II. Nutritional ecology 750 III. Cooperation and conflict in ant–plant symbioses 754 IV. Ant–plant symbioses in a changing world 758 V. Prospects 759   Acknowledgements 760   References 761